The Production of Pro-angiogenic VEGF-A Isoforms by Hypoxic Human NK Cells Is Independent of Their TGF-β-Mediated Conversion to an ILC1-Like Phenotype - Hawke, Lindsey G.; Whitford, Mara K. M.; Ormiston, Mark L. (Frontiers in Immunology, 2020)
Circulating natural killer (NK) cells have been shown to adopt a type 1 innate lymphoid cell (ILC1)-like phenotype in response to TGF-β and secrete VEGF-A when exposed to hypoxia. Although these changes are often considered to be linked attributes of tissue residency, it has yet to be determined if TGF-β and hypoxia work in concert to coordinate NK cellular phenotype and angiogenic potential. Examination of human circulating NK cells treated with TGF-β demonstrated heterogeneity in their potential to adopt an ILC1-like phenotype, as indicated by the upregulation of CD9 and CD103 on only a subset of cells in culture. Culturing NK cells in chronic hypoxia did not induce a similar ILC1-like conversion and did not enhance the degree of conversion for cells exposed to TGF-β. Similarly, hypoxic culture of circulating NK cells induced VEGF-A secretion, but this production was not enhanced by TGF-β. Fluorescent in-situ hybridization flow cytometry demonstrated that hypoxia-induced VEGF-A production was uniform across all NK cells in culture and was not a selective feature of the cellular subset that adopted an ILC1-like phenotype in response to TGF-β. Examination of VEGF-A isoforms demonstrated that hypoxia induces the production of pro-angiogenic VEGF-A isoforms, including VEGF-A165 and VEGF-A121, and does not stimulate any meaningful production of anti-angiogenic isoforms, such as VEGF-Ab transcriptional variants or VEGF-Ax. In summary, TGF-β-mediated ILC1-like conversion and hypoxia-induced VEGF-A production are discrete processes in NK cells and are not part of a linked cellular program associated with tissue residency.